Factors Affecting Towards Decision to Use Services of Luang Prabang Night Garden: https://doi.org/10.69692/SUJMRD100493 - BOUNTHACHIT, Bounthany; YANGSENXAY, Chahue; Somsackxaysompheng, Oulavieng (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research is to: 1) to study the situation of using restaurant services in Luangprabang Night garden restuarant, 2) to study the opinions of customers about Luangprabang Night garden restuarant 3) to find out the factors affect the decision to use services of Luangprabang Night garden restaurant. It was a survey research by using a questionnaire as a tool to collect and compile data from a sample group of 385 people. Use the SPSS version 20 program to find the frequency, percentage, mean value, standard deviation, and multiple regression equation to analyze the factors that affect the decision to use services this restaurant. The results of the research found that the situation of the Luangprabang Night garden restuarant are that most of the consumers go to use service 1-2 times per month, and some go to there every day for a week. The busiest time is between 6 o'clock and 8 o'clock in the evening. The opinion from the service users about Lat Lat Restaurant in the capital city is that after the customers have eaten at Luangprabang Night garden restuarant, they have the idea of ​​recommending, persuading, and rewarding people they know to use the service and they think that they will come back to this place again. Also, the custommers have taken photos and record videos of Luangprabang Night garden restuarant to share on Facebook (Facebook), Page, Website, etc. in order to persuade others to come to service. At the same time, they also think that Luangprabang Night garden restuarant is the best place for having dinner outside of home and they are very satisfied after the customers decide to use Luangprabang Night garden restuarant. The factors affect the decision to use Luangprabang Night garden restuarant are product factors, price factors, marketing promotion factors, operational process factors, physical characteristics factors and location factors with a statistical significance level of Sig <0.05.